Intravenous Versus Topical Tranexamic Acid in Total Knee Arthroplasty: Both Effective in a Randomized Clinical Trial of 640 Patients. (20th June 2018) - Abdel, Matthew P.; Chalmers, Brian P.; Taunton, Michael J.; Pagnano, Mark W.; Trousdale, Robert T.; Sierra, Rafael J.; Lee, Yuo-yu; Boettner, Friedrich; Su, Edwin P.; Haas, Steven B.; Figgie, Mark P.; Mayman, David J.
Abstract : Background: Tranexamic acid (TXA) reduces bleeding and the need for transfusion after total knee arthroplasty. Most literature has focused on intravenous (IV) administration of TXA, with less data available on the efficacy of topically administered TXA. This multicenter randomized clinical trial specifically assessed the efficacy of topical TXA compared with IV TXA as measured by calculated blood loss, drain output, and transfusion rates. Complications, including venous thromboembolism (VTE), were reported. Methods: A total of 640 patients who underwent primary unilateral total knee arthroplasty for osteoarthritis at 2 large academic centers were randomized to receive 1 g of IV TXA prior to tourniquet inflation and 1 g at closure, or 3 g of TXA diluted in 45 mL of normal saline solution (total volume of 75 mL) and topically applied after cementation. Age, sex, body mass index, American Society of Anesthesiologists (ASA) score, and preoperative hemoglobin level were similar between the groups. Univariate, multiple linear regression, and multiple logistic regression analyses were performed. Results: Patients who received topical TXA had significantly greater calculated blood loss compared with those who received IV TXA (mean of 324 compared with 271 mL; p = 0.005). Drain output was significantly higher in the topical TXA group compared with the IV TXA group (mean of 560 compared with 456 mL; p < 0.0001). The rate of transfusion was low in the topical and IV groups, with no significant difference on univariate analysis (1.6% compared with 0.6%, respectively; p = 0.45); however, on multiple logistic regression analysis, patients who received topical TXA were 2.2-fold more likely to receive a transfusion (p < 0.0001). The topical and IV TXA groups did not differ significantly with respect to the rate of thrombotic events (0.6% compared with 1.6%, respectively; p = 0.45). Conclusions: In this large, randomized clinical trial involving patients undergoing total knee arthroplasty, both IV and topical TXA were associated with a low rate of transfusion. While IV TXA was associated with less calculated blood loss, lower drain output, and fewer transfusions, the small differences between the groups may not be clinically important. Given the low prevalence of thrombotic complications, the relative safety of one formulation of TXA over the other cannot be definitely established. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.